Effect of Ice Cream Given Secang Wood Extract (Caesalpinia Sappan L.) on the Intensity of Disminorea Pain in Young Women in the Kunduran Puskesmas Area Blora District - Puspitawati, Dwi Apriliani; Mardiyono, Mardiyono; Indrati, Dina; Nurul, Melyana; Supriyana, Supriyana (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Dysmenorrhea is pain during menstruation, the cause in the blood is an imbalance of progesterone hormones, prostaglandins and stress / psychological factors that cause dysmenorrhea in women. Interventions that can be applied in dealing with the above problem is the provision of herbal therapy ice cream secang wood extract.  This research to proved the benefits of Secang Wood Extract Ice cream (Caesalpinia Sappan L.) with vitamin E supplements on reducing Dysmenorrhea Pain Intensity in Adolescent Girls.  This research is true experimental using pre-post test approach with control group design. Sampling was done with simple random sampling technique obtained 62 adolescent girls, Statistical analysis used Paired T - Test and Wilcoxon, and Mann Whitney U.  Gave ice cream Secang Wood Extract dose of 100 grams / cup with the content of secang wood extract 246.7 mg / 60 kgBB before and after against Dysmenorrhea Pain with p value (p = 0.000 <0.05), meaning there is a difference between before and after consumption of Secang Wood Extract Ice cream (Caesalpinia Sappan L.). The difference test in the Intervention group shows a meaningful difference with a value of(p = 0.000), meaning that the administration of Secang Wood Extract Ice cream (Caesalpinia Sappan L.) and has an effect on reducing the intensity of dysmenorrhea pain in adolescent girls.  The Conclusion is the content of brazilin (40 mg) and flavonoids (1.47mg) in the ice cream preparation of Secang Wood Extract in the size of 100 grams can reduced the pain level of dysmenorrhea. Keywords: Ice cream, Secang, Adolescents, Dysmenorrhea, Vitamins